2016
DOI: 10.1016/j.proeng.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

An Internet-of-Things (IoT) System Development and Implementation for Bathroom Safety Enhancement

Abstract: Statistics show that a bathroom is one of the most hazardous places especially for older people. Older people typically have greater difficulties with mobility and balance, making them more vulnerable to fall and slip injuries in a bathroom and causing serious health issues related to short and long-term well-being. Various components in a bathroom including shower, tub, floor, and toilet have been re-designed, and independently upgraded their ergonomics and safety aspects; however, the number of bathroom inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 1 publication
0
12
0
3
Order By: Relevance
“…The other 39 papers used other types of sensors, among which audio recorders, video/image recorders, radar sensors, inertial measurement unit (IMU) sensors (accelerometer and/or gyroscope) attached to the object instead of the human body and environmental sensors. Audio recorders were used for detecting activities related to water flowing, e.g., washing hands [ 35 , 36 , 37 , 38 , 39 ], washing face [ 36 ], toileting [ 38 , 40 , 41 ] or bathing [ 40 ]. Video/image recorders were usually used for detecting washing hands [ 35 , 39 , 42 , 43 , 44 ], washing face [ 36 ] and dressing [ 45 , 46 , 47 , 48 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other 39 papers used other types of sensors, among which audio recorders, video/image recorders, radar sensors, inertial measurement unit (IMU) sensors (accelerometer and/or gyroscope) attached to the object instead of the human body and environmental sensors. Audio recorders were used for detecting activities related to water flowing, e.g., washing hands [ 35 , 36 , 37 , 38 , 39 ], washing face [ 36 ], toileting [ 38 , 40 , 41 ] or bathing [ 40 ]. Video/image recorders were usually used for detecting washing hands [ 35 , 39 , 42 , 43 , 44 ], washing face [ 36 ] and dressing [ 45 , 46 , 47 , 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…IMU sensors were attached to the water pipe for detecting washing and bathing [ 52 ], on the robot for detecting dressing [ 46 ], and in the soap bar for hand washing [ 37 ]. Multiple environmental sensors were combined for detecting bathing/showering [ 34 , 36 , 40 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ], toileting [ 34 , 36 , 38 , 40 , 41 , 55 , 56 , 57 , 58 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ], dressing [ 45 , 58 , 71 , 72 ], general personal hygiene activity [ 54 , 61 ], washing hands [ 36 , 37 , 38 ], washing face [ 36 ] and grooming [ 58 , 70 ].…”
Section: Methodsmentioning
confidence: 99%
“…Kamar mandi yang dipantau sudah dilengkapi dengan sistem otomasi yang hampir mengatur semua variabel kebutuhan dalam kamar mandi. [5] Penelitian Koo et al, (2016), menggunakan integrasi beberapa sensor dan aktuator. Setiap sensor memiliki tugas yang independen untuk berkerja sesuai dengan variabelnya.…”
Section: Tinjauan Pusakaunclassified
“…Setiap sensor memiliki tugas yang independen untuk berkerja sesuai dengan variabelnya. [5] Semua aktuator bekerja dibawah algoritma pengendalian yang dikembangkan secara mandiri. Semua kesesuaian kerja ini menjadi sebuah sistem yang terbangun untuk menjalankan tujuan sebagai peningkat aspek keamanan dalam kamar mandi.…”
Section: Tinjauan Pusakaunclassified
“…Undoubtedly, statistics have shown that many of injuries among elderly are first discovered from toilet and bathroom incidents. Thus, the authors [8] have presented a holistic conceptual approach of an IoT system development and implementation for bathroom safety enhancement. A typical sensor module consists of four (4) main components including power supply, sensor, actuator and communication port is designed.…”
Section: Figure 1 Sample Of Mounted Automated Tissue Dispensermentioning
confidence: 99%